The capitalist man of the 21st century - Auccatoma Tinco, Roly (2019)
Every capitalist man of the 21st century, known as an absolute subject or spirit, must have three indispensable qualities and capacities: the spirit of domination, the will to power, and the drive to kill. Hegel founds the absolute subject and Nietzsche states that it is possible to become a superman by stating: “I announce the Superman to you. Man is something that must be overcome ”,“ Man is a rope stretched between the beast and the Superman: a rope over an abyss ”and“ The greatest thing about man is that he is a bridge and not a goal. What we must love in man is that it consists of a transition and not a sunset ”(Nietzsche, F. 2003, p. 38-40). The capitalist man of the 21st century is the globalizer, he is the Hegelian absolute spirit and the Nietzschean superman who must dominate and totalize the world for himself; his will to power tells him: moving forward is power, stopping is dying, and he also has the drive to kill; the capitalist man is a spirit that denies everything, in his essence he carries negativity. In short, these three qualities of the spirit of the master is necessary to understand and thus understand the effects of their actions such as globalization, global warming and nuclear weapons.